Hypertension Prevention and Treatment Counseling with Acupressure Therapy In Suka Maju Village, Penarik District, Mukomuko Regency - Sunarsih; Damanik, Refiani; Marpaung, Pita; Sari , Siska Yulia Karmila; Situmorang , Ronalen (Jurnal Inovasi Kerja Nyata, 2025)
Hypertension is still a global target, to reduce hypertension patients in 2010 to 2030 (WHO, 2021). Hypertension is often referred to as high blood pressure, a condition in which there is an increase in blood pressure in abnominal arteries that occurs repeatedly with an increase in systolic pressure of more than or equal to 140 mmHg and an increase in diastolic pressure of more than or equal to 90 mmHg (Sriyanti, 2022). One of the non-pharmacological treatments for hypertension is acupressure therapy. Simulation at acupressure points can stimulate the release of histamine as a mediator of vasodilation and decreased vascular resistance (Arfian, and Heriviyatno J Siagian, 2021). This KKN-T activity is a form of community service that aims to improve the knowledge, awareness and behaviour of the RT 04 community of Suka Maju Village about the risk of hypertension. This activity is in accordance with the priority program in accelerating efforts to prevent and treat hypertension, which is also emphasized in the UPTD Puskesmas Penarik program. The programme was carried out through educational methods, blood pressure checks and acupressure therapy carried out in RT 04 Suka Maju Village, Penarik Kab.Mukomuko Bengkulu with the target community, the elderly, people with hypertension and cadres totalling 44 people. The community has received information about the causes, signs and symptoms, prevention and non-pharmacological treatment of hypertension with acupressure therapy. The results of this activity showed an increase in community knowledge about Hypertension, prevention and application of acupressure therapy to lower blood pressure and reduce head pain in people with hypertension. This helps the community to better understand Hypertension and take appropriate preventive measures. It is expected that the community can apply prevention and acupressure therapy for the treatment of Hypertension in Suka Maju Village.